Evaluation of Kluyveromyces spp. for conversion of lactose in different types of whey from dairy processing waste into ethanol - Ohstrom, Ashley Mae; Buck, Autumn Elizabeth; Du, Xue; Wee, Josephine (Frontiers in Microbiology, 2023)
The processing of dairy products currently generates significant amounts of waste, particularly in the form of liquid whey. The disposal of whey poses a challenge to the environment due to its high organic content and biological oxygen demand. Whey contains lactose, soluble proteins, lipids, and minerals. While Saccharomyces cerevisiae can efficiently utilize glucose, they are unable to metabolize lactose. In contrast, Kluyveromyces spp. encode two genes, Lac12 and Lac4 that enable conversion of lactose to other by-products such as ethanol. Here, we selected five Kluyveromyces yeast inoculated into three different types of whey substrates, cheddar sweet whey, cream cheese acid whey, and yogurt acid whey that could be used to convert lactose into ethanol. We demonstrate that differences exist in ethanol production across different whey substrates inoculated with Kluyveromyces yeast. In sweet whey, K. lactis, K. lactis Y-1205 and K. lactis Y-1564 were the highest ethanol producing strains. The highest amount of ethanol produced was 24.85 ± 3.5 g/L achieved by Y-1564 in sweet whey (96.8% efficiency). K. lactis Y-1205 produced 22.39 ± 5.6 g/L ethanol in yogurt acid whey. In cream cheese acid whey, K. lactis strains produced significantly higher ethanol levels compared to S. cerevisiae and K. marxianus (p < 0.05). Outcomes from this study could provide a simple and cheap solution for small- to medium-sized dairy processing facilities to ferment lactose in whey into ethanol using lactose-consuming yeasts.